1993
DOI: 10.1152/ajpendo.1993.265.5.e708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endurance training on plasma free fatty acid turnover and oxidation during exercise

Abstract: Plasma free fatty acid (FFA) levels tend to be lower and the plasma lipolytic hormone response to prolonged exercise of the same intensity is blunted after endurance exercise training. To determine whether training elicits a corresponding decrease in plasma FFA turnover and metabolism during prolonged exercise, we measured plasma [1-13C]palmitate kinetics and oxidation and respiratory gas exchange in 13 subjects during the latter portion of a 90- to 120-min bout of cycle ergometer work performed before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
139
7
8

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(166 citation statements)
references
References 21 publications
12
139
7
8
Order By: Relevance
“…Thus, trained subjects have a higher fat oxidative capacity, lower RQ during submaximal exercise and improved fatty acid handling. [15][16][17][18] In a recent study, we showed that a 3-month low-intensity endurance training program in previously untrained, sedentary males improved fat oxidative capacity and lowered plasma triglyceride levels. 18 In the present study, we could not detect any changes in fat oxidative capacity at the whole body level, probably due to the shortterm nature of the present training program.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, trained subjects have a higher fat oxidative capacity, lower RQ during submaximal exercise and improved fatty acid handling. [15][16][17][18] In a recent study, we showed that a 3-month low-intensity endurance training program in previously untrained, sedentary males improved fat oxidative capacity and lowered plasma triglyceride levels. 18 In the present study, we could not detect any changes in fat oxidative capacity at the whole body level, probably due to the shortterm nature of the present training program.…”
Section: Discussionmentioning
confidence: 98%
“…Resting days were incorporated on days 4 and 10. After the training session, subjects again followed a standardization period for 3 days (days [15][16][17], with the same standardization diet as on days 1-3 and during which subjects refrained from exercise. In the afternoon of day 17, the subjects again performed a submaximal exercise test at 40% W max , with substrate oxidation being measured and blood being sampled.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…exertion; free fatty acid; glucose; lactate; crossover concept; substrate shuttling EFFECTS OF EXERCISE intensity and training state on muscle lipid metabolism in humans are unclear, as the relatively few studies have utilized different experimental approaches. Some investigations have employed isotopic tracers and indirect calorimetry (25,29,33), whereas others have utilized arteriovenous (a-v) balance methods (17,22,35) and muscle biopsies (18,22 …”
mentioning
confidence: 99%
“…isotopic tracers and indirect calorimetry (25,29,33), whereas others have utilized arteriovenous (a-v) balance methods (17,22,35) and muscle biopsies (18,22). In addition, longitudinal and cross-sectional designs have been employed that have tested trained and untrained subjects at either the same absolute or relative exercise intensity, but rarely both.…”
mentioning
confidence: 99%